2018
DOI: 10.1002/biof.1405
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery system enhanced the bioavailability of stilbenes: Resveratrol and pterostilbene

Abstract: Stilbenes are a large group of compounds with the C C C skeleton, in which two aromatic rings are connected by an ethylene bridge. Resveratrol and its structural analog, pterostilbene, are by far the two most widely researched stilbenes in terms of their beneficial bioactivities. However, the bioefficacy of these compounds is greatly reduced when consumed orally due to their poor aqueous solubility, which leads to poor bioavailability. To overcome the limitation, strategies improving their solubility, absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 77 publications
(79 reference statements)
0
24
0
Order By: Relevance
“…The uniqueness of our findings lie in the fact that we were able to show through 16S rRNA gene sequencing and fecal transfer experiments that the effectiveness of resveratrol against colitis could be explained by the ability of this natural product to alter and reverse microbial dysbiosis and SCFA production to promote an anti‐inflammatory effect (induction of Treg/IL‐10) and suppress the inflammatory (Th1/Th17) T cell response, something that has not been reported in the literature thus far. It is particularly interesting to note that the poor bioavailability of resveratrol during oral consumption, which is attributed to the weak aqueous solubility of the compound, has always been an issue in terms to suggesting this natural product as a treatment of various disease . In fact, this observation has led to a wealth of research focusing on how to increase the bioavailability of this potent anti‐inflammatory natural product so that it can be absorbed and circulated to various affected organs, such as by way of encapsulation in nanoparticles or some other vehicle .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The uniqueness of our findings lie in the fact that we were able to show through 16S rRNA gene sequencing and fecal transfer experiments that the effectiveness of resveratrol against colitis could be explained by the ability of this natural product to alter and reverse microbial dysbiosis and SCFA production to promote an anti‐inflammatory effect (induction of Treg/IL‐10) and suppress the inflammatory (Th1/Th17) T cell response, something that has not been reported in the literature thus far. It is particularly interesting to note that the poor bioavailability of resveratrol during oral consumption, which is attributed to the weak aqueous solubility of the compound, has always been an issue in terms to suggesting this natural product as a treatment of various disease . In fact, this observation has led to a wealth of research focusing on how to increase the bioavailability of this potent anti‐inflammatory natural product so that it can be absorbed and circulated to various affected organs, such as by way of encapsulation in nanoparticles or some other vehicle .…”
Section: Discussionmentioning
confidence: 84%
“…It is particularly interesting to note that the poor bioavailability of resveratrol during oral consumption, which is attributed to the weak aqueous solubility of the compound, has always been an issue in terms to suggesting this natural product as a treatment of various disease. 68 In fact, this observation has led to a wealth of research focusing on how to increase the bioavailability of this potent anti-inflammatory natural product so that it can be absorbed and circulated to various affected organs, such as by way of encapsulation in nanoparticles or some other vehicle. 69,70 However, our findings suggest that resveratrol alters the microbiome directly and this leads to the anti-inflammatory effects during colitis, even before it becomes bioavailable to various organs after oral consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In rabbits, for instance, its half-life in plasma is only 14 min [34]. Resveratrol’s bioavailability can be partly enhanced by combining it with other phytochemicals e.g., piperine [35], or by using either controlled-release devices or nanotechnological formulations [31,36,37,38]. Resveratrol is, in humans, quickly converted to sulfate- and glucuronide conjugated forms, mainly to resveratrol-3-O-sulfate , resveratrol-4′-O-glucuronide , and resveratrol-3-O-glucuronide [26,39], and these metabolites may provide an intracellular reservoir for the generation of parent resveratrol [40].…”
Section: Introductionmentioning
confidence: 99%
“…Pterostilbene ( trans -3,5-dimethoxy-4′-hydroxystilbene) is a natural phytoalexin mainly found in blueberries and Pterocarpus marsupium heartwood; chemically, it is a dimethyl ether analog of resveratrol. However, the pharmacological activities (in vitro and in vivo) of pterostilbene are usually better than those of resveratrol [ 2 ], as the methoxyl groups at positions 3- and 5- enhance membrane permeability and metabolic stability [ 3 ]. It is well reported that pterostilbene possesses excellent pharmacological benefits for the prevention and treatment of various types of cancer [ 4 , 5 ], Alzheimer’s disease [ 6 ], vascular dementia [ 7 ], obesity [ 8 ] or diabetes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%